Work-related Injury among Welders Working in Metal Workshops of Dharan Municipality, Nepal - Ghimire, Anup; Budhathoki, Shyam Sundar; Niraula, Surya Raj; Shrestha, Abha; Pokharel, Paras K (Journal of Nepal Health Research Council, 2018)
Background: Injuries are a problem worldwide in all occupations. Welders are exposed to many hazards at work resulting in a variety of health problems including injuries at work. This study was conducted to find out the prevalence and factors associated with injuries among welders in Dharan city of eastern Nepal.Methods: A cross sectional study was conducted among 86 welders in Dharan city. Occurrence of injury in past 2 weeks and past 12 months were recorded. Data regarding sociodemographic along with occupational characteristics was collected using semi structured questionnaire. Data analysis was done using SPSS version 17.Results: All the welders in this study were male with almost half of the welders under the age of 25 years and about a fifth (21.1%) of the welders having received some form of welding training. In the past 12 months, 21.1% of the welders suffered from work related injuries. More than 95% welders used at least one personal protective equipment in this study. More injuries were seen among welders with age ≥35 years, working experience ≥ 5 years, not received training and not using of PPE at work. However, these factors were not found to be statistically significant.Conclusions: Work related injuries are high among welders of Dharan. Further research is required to explore the relationship between age, literacy, training and use of personal protective equipment with the occurrence of injuries among the welders.